Role of Carbon Nanotubes for Plant Growth Regulation: A Review - Tiwary Mukesh; Waman Mohan; Ashok Kumar Jha (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
This review highlights the role of carbon nanotubes are vital for plant growth regulation. A carbon nanotube (CNT) is a tubular structure made of carbon atoms, having a diameter of nanometer order but a length in micrometers. CNTs are allotropes of carbon with a nanostructure that can have a length-to-diameter ratio greater than 1,000,000. These cylindrical carbon molecules have unique features that could make them valuable in a variety of nanotechnology applications. Formally generated from the grapheme sheet, they have exceptional mechanical qualities such as high toughness and elastic modulus. In terms of electronic structure, they display both semiconducting and metallic behavior, covering the entire range of attributes relevant to technology. There are two types of nanotubes: single-walled and multi-walled. Techniques have been developed to produce Nanotubes in sizeable quantities, including arc discharge, laser ablation, chemical vapor deposition, silane solution method and flame synthesis method. The properties and characteristics of CNTs are still being researched heavily and scientists have barely begun to tap the potential of these structures. Without a doubt, carbon nanotubes represent a material that offers great potential, bringing with it the possibility of breakthroughs in a new generation of devices, electric equipment and biofields. Multi-walled carbon nanotubes (CNTs) can affect plant phenotype and the composition of soil microbiota. Tomato plants grown in soil supplemented with CNTs produce two times more flowers and fruit compared to plants grown in control soil. Carbon/fullerene nanotechnology is a rapidly growing area of research that finds use in plants, medicine and engineering. Carbon nanotubes (single-wall carbon nanotubes and multi-wall carbon nanotubes) in many cases can penetrate the seed coat and plant cell wall which depends on their size, concentration and solubility. The future prospect of carbon nanomaterials is fairly bright as it is a low-cost solution to increase crop production and fruit manifold.